Progranulin haploinsufficiency causes biphasic social dominance abnormalities in the tube test. (5th July 2016) - Arrant, A. E.; Filiano, A. J.; Warmus, B. A.; Hall, A. M.; Roberson, E. D.
Abstract : Loss‐of‐function mutations in progranulin ( GRN ) are a major autosomal dominant cause of frontotemporal dementia (FTD), a neurodegenerative disorder in which social behavior is disrupted. Progranulin‐insufficient mice, both Grn +/− and Grn −/−, are used as models of FTD due to GRN mutations, with Grn +/− mice mimicking the progranulin haploinsufficiency of FTD patients with GRN mutations. Grn +/− mice have increased social dominance in the tube test at 6 months of age, although this phenotype has not been reported in Grn −/− mice. In this study, we investigated how the tube test phenotype of progranulin‐insufficient mice changes with age, determined its robustness under several testing conditions, and explored the associated cellular mechanisms. We observed biphasic social dominance abnormalities in Grn +/− mice: at 6–8 months, Grn +/− mice were more dominant than wild‐type littermates, while after 9 months of age, Grn +/− mice were less dominant. In contrast, Grn −/− mice did not exhibit abnormal social dominance, suggesting that progranulin haploinsufficiency has distinct effects from complete progranulin deficiency. The biphasic tube test phenotype of Grn +/− mice was associated with abnormal cellular signaling and neuronal morphology in the amygdala and prefrontal cortex. At 6–9 months, Grn +/− mice exhibited increased mTORC2/Akt signaling in the amygdala and enhanced dendritic arbors in the basomedial amygdala, and at 9–16 months Grn +/− mice exhibited diminished basal dendritic arbors in the prelimbic cortex. These data show a progressive change in tube test dominance in Grn +/− mice and highlight potential underlying mechanisms by which progranulin insufficiency may disrupt social behavior. Abstract : Biphasic tube test abnormalities in Grn +/− mice are associated with altered rpS6/mTORC2/Akt signaling and dendritic arbors in the amygdala and prelimbic cortex.